Family Life in Islam - Khurshid Ahmad (The Islamic Foundation, 1974)
Islam is a complete way. It has a distinct outlook on life. It gims at producing a unique personality in the individual and a distinct culture for the community based on Islamic ideals and values.The institutians of marriage and the faimily occupy a very important position in this scheme of life. An effort is being made in this small book to explain the Islamic concept of marriage and the family. The original inspiration for this essay came from a recent conference. The Standing Conference on Christian-Muslim Dialogue organised a three day conference at Wood Hall, Wetherby, Yorks, on the family in Christianity and Islam.